A Spatial Analysis of Selected Art: a GIScience-Humanities Interface. Issue 1 (March 2020) - Griffith, Daniel A.
Abstract : This exposition presents little-known connections between geography, through geographic information systems (GISs), mathematics, through matrix algebra, and art, through paintings and images, adding to the geo-humanities, spatial humanities, and humanistic mathematics literature. To this end, findings summarized for spatial statistical analyses of selected Susie Rosmarin paintings (which are reminiscent of visualizations of certain mathematical quantities known as eigenvectors), remotely sensed images that have appeared in art exhibits, and selected famous paintings by historically renowned artists reveal that spatial autocorrelation constitutes a fundamental element of art. These analyses extend the tradition of visualizing fractals as art, and interfacing cartography with art. This paper promotes analytical art, and establishes additional commonalities for GIScience, mathematics, and art.